Issues in multi-agent systems : the AgentCities, ES experience - Moreno, Antonio (Springer, 2017)
The agent paradigm has been a subject of research for the last years, and the purpose of this book is to present current status of this technology by looking at its application in different domains, such as electronic markets, e-tourism, ambience intelligence, and complex system analysis.